Design, Production and Comparison with Theoretical Calculations of a Uniform Electromagnetic Field Generator with Helmholtz Coils - Avcı, Ferdi; Ağrali, Emin; Yaman, Orhan; Çavaş, Mehmet (Niyazi BULUT, 2025)
Helmholtz coils, which are widely used in the scientific world, are used to generate a uniform magnetic field (EMF). It is used in many test applications due to its ability to generate EMF at the desired frequency. It is easier to work with these coils at low frequencies. Since their inductance and internal resistance will be low due to the low frequency, the intended EMF can be obtained by supplying enough current to the coils. Helmholtz coils are used in many areas such as electromagnetic interference tests, biomedical experiments, physics experiments, instrument calibration. In this study, an EMF generator operating in alternative current was designed and manufactured for different EMF generation between 1 mT and 2 mT. Helmholtz coils with circular geometry were manufactured for the EMF generator. The fabricated helmholtz coils are positioned on the vertical axis. A current of 21 A will be passed through the helmholtz coil, which is the maximum value for 2 mT. 2.2 mm conductor cross-section was selected for passing 21 A current. At 21 A, it was found to operate without heating. The radius of the Helmholtz coil was preferred as 15 cm. The conductor weight used in the Helmholtz coil is 1000 g in total. The results of the theoretical calculations for the EMF generator and experimental measurements on the fabricated prototype were tabulated and graphs were obtained. They were compared graphically and the difference between their values was analyzed.
Keywords: Metrology; Applied and Industrial Physics; Metroloji; Uygulamalı ve Endüstriyel Fizik